Passive Smoking is Responsible for Disease Activity in Female Patients With Rheumatoid Arthritis - Seong Kyu KIM,; Jung Yoon CHOE, (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the effects of passive smoking on disease activity in female patients with rheumatoid arthritis (RA). Patients and methods: Among a total of 191 female patients with RA (mean age 59.1±12.5 years; range 21 to 87 years) consecutively recruited, 100 female patients (mean age 56.1±13.4 years; range 21 to 87 years) completed the study with mean 17.3 months of follow-up. Patients were classified according to smoking status: current, never, passive, or ex-smoker. Clinical response between never and passive smokers was assessed by disease- activity score 28 (DAS28)-erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) (DAS28-ESR and DAS28-CRP) and by the European League Against Rheumatism response criteria. Results: Among the 100 female RA patients analyzed, the distribution of smoking status was as follows: current (n=3), never (n=55), passive (n=34), and ex-smokers (n=8). There was no difference of DAS28-ESR and DAS28-CRP between never and passive smokers at baseline. At the time of follow-up, the values of DAS28-ESR and DAS28-CRP in never smokers were significantly decreased than those in passive smokers (p=0.019 and p=0.023, respectively). Patients who never smoked showed a trend to have good or moderate European League Against Rheumatism response without statistical significance, compared to passive smokers (52.7% vs. 32.4%, respectively; p=0.060). Conclusion: This preliminary study implicates that passive smoking might be responsible for higher disease activity in female RA patients and never smoking might induce good clinical response in RA.